Quem cuida de quem cuida: o acesso de trabalhadoras domésticas à assistência social durante a pandemia de COVID-19 em Sergipe - Rocha, Larissa Feitosa da (2023)
In some Brazilian states, paid domestic work was considered an essential activity, forcing workers to continue working, exposing these women to contamination by SARS-CoV-2 when traveling on public transport and in work environments. In other words, a Covid-19 pandemic highlighted situations that were already well established in Brazil but made invisible: the exploitation of domestic workers and the unequal relationship with their employers. Over the past three years, Brazilian media has widely reported cases of domestic workers being rescued from working in conditions similar to slavery, as well as deaths resulting from Covid-19 contamination in the workplace. As was the case of Cleonice Gonçalves, the first victim of the disease in Niterói-RJ, who died after contracting the virus from her employers. In addition to the case of Miguel Otávio, who died because his physical and emotional integrity was neglected by his mother's boss, who was on duty. This scenario, as already mentioned, revealed the inequalities that are produced by domestic work in Brazil, having origins in the colonial period with slavery, and even after abolition, reverberating to the present day. In Brazil, paid domestic work has a determined race, gender and class. Placing working-class black women at the base of the pyramid of exploitation and victims of the various inequalities promoted by our society. Given this, we question the role of the State in guaranteeing social protection for these workers through social assistance and other public policies. Therefore, this research aims to analyze domestic workers' access to social assistance in the state of Sergipe during the covid-19 pandemic. To achieve this objective, we list as objectives specific: a) historically analyze the role of domestic work in Brazilian social formation and the development of capitalism in Brazil; b) characterize the profile of domestic workers in Brazil at the same time; c) collect statistical data on social assistance policy in Sergipe; d) analyze the responses that the State gave in relation to the social protection of domestic workers during the covid-19 pandemic in Brazil. We use dialectical historical materialism as a method of analysis to understand the concrete reality through the contradictory movement of history. The research was documentary in nature and for this, as a data source, we carried out a bibliographic and documentary survey, data from research and statistical institutions such as PNAD, IBGE, scientific and journalistic articles, theses and dissertations. In partnership with SINDOMÉSTICA, we collected data from 50 domestic workers from various regions of the state of Sergipe. The investigation was characterized by descriptive research and for data collection and analysis, it had quantitative and qualitative characteristics. As a result of this research, we assessed that the social policy implemented by the state government during and after the covid-19 pandemic is welfare-based and the lack of coordinated actions and techniques for effective social protection programs and policies contribute to this characteristic.